The effect of vortex well thickness on microstructure and mechanical properties of aluminium LM6 - Hehsan, Haffidzudin (2013)
Gating system in a casting mold consists of a series of channels and reservoirs designed to feed molten metal to all parts of the mold cavity. The design of the system is the principle means by which the mold designer can control the rate of the metal flow and promote the desirable temperature distribution of cooling that will take place within the filled cavity. Many extensive research efforts and works have been made and reported on gating system design. However, the significance affects of vortex gating system design to the microstructure and mechanical properties of Aluminium casting has rarely been reported. This research was conducted to determine the effects of vortex well thickness on the microstructure and mechanical properties of Aluminium LM6 in sand casting process. Microstructure analysis has been conducted using Optical Microscope and Scanning Electron Microscopic (SEM) to examine the microstructure and defects pattern of selected casting specimens produced from different vortex well thickness. Three (3) Point Bending Test have been conducted to determine the affects of different well thickness on the flexural strength of the casting material. Weibull Distribution Analysis method has been utilized to quantify the variability of strengths in the cast material. The experimental and testing results show that increasing the vortex well thickness leads to a significance improvement on the flexural strength of the cast material. In addition, casting defects such as shrinkage porosity and gas porosity would be minimized as the thickness of the vortex well increases.